2017
DOI: 10.1021/acs.chemrev.6b00614
|View full text |Cite
|
Sign up to set email alerts
|

Odyssey of Multivalent Cathode Materials: Open Questions and Future Challenges

Abstract: The rapidly expanding field of nonaqueous multivalent intercalation batteries offers a promising way to overcome safety, cost, and energy density limitations of state-of-the-art Li-ion battery technology. We present a critical and rigorous analysis of the increasing volume of multivalent battery research, focusing on a wide range of intercalation cathode materials and the mechanisms of multivalent ion insertion and migration within those frameworks. The present analysis covers a wide variety of material chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
1,039
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,008 publications
(1,064 citation statements)
references
References 340 publications
20
1,039
0
5
Order By: Relevance
“…1,2 Indeed, for divalent charge carriers, the number of ions that must react to achieve a certain electrochemical capacity should diminish by a factor of two when compared to monovalent ions such as lithium or sodium, or, for the same number of reacted ions there would be a concomitant two-fold increase in the energy density of the cells. Furthermore, the exploitation of naturally abundant elements, such as Ca, Mg and Al in replacement of conventional Li-ion battery chemistry would bear substantial environmental and cost benefits.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Indeed, for divalent charge carriers, the number of ions that must react to achieve a certain electrochemical capacity should diminish by a factor of two when compared to monovalent ions such as lithium or sodium, or, for the same number of reacted ions there would be a concomitant two-fold increase in the energy density of the cells. Furthermore, the exploitation of naturally abundant elements, such as Ca, Mg and Al in replacement of conventional Li-ion battery chemistry would bear substantial environmental and cost benefits.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only a few types of conventional intercalation materials have been identified that are capable of storing Mg 2+ ions reversibly. [8][9][10][11][12][13][14][15] Thus, the challenges to realize the rechargeable Mg battery technology are not only the improvement of the electrolyte toward high oxidative stability, but also the discovery of cathode materials enabling high performance of Mg batteries.…”
Section: Magnesium Batterymentioning
confidence: 99%
“…The research work on Mg batteries in general has been timely reviewed and thoroughly discussed, [8][9][10][11][12][13][14][15][18][19][20] so that we will focus on the properties of Mg electrolytes in view of the application to S cathodes. Thereafter, we will illustrate the progress that is being made on Mg-S battery and discuss future prospects for high-energy Mg and Mg-S batteries.…”
Section: Magnesium Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…This low barrier is verified by ab initio molecular dynamics and kinetic Monte Carlo simulations. The voltage and specific energy are predicted to be B1.98 V and B173 W h kg A promising strategy to increase the energy density of rechargeable batteries is to transition from monovalent to multivalent batteries, such as Mg batteries, [1][2][3] Fig. 1), we also investigated other possible sites for Mg to reside in the empty host structure Mo 3 (PO 4 ) 3 O.…”
mentioning
confidence: 99%